2008
DOI: 10.1007/s00059-008-3097-1
|View full text |Cite
|
Sign up to set email alerts
|

Trends im Einsatz von Drug-eluting Stents im klinischen Alltag in Deutschland

Abstract: : DES were mainly applied in a stable situation (Figure 2), but were also increasingly used for complex coronary interventions in off-label indications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…1 In the United States (U.S.) alone, an estimated 600,000 PCIs are performed annually at a direct cost of approximately $30 billion, 2-4 with similar trends in Europe and Canada. 5-7 The growth of PCI in the U.S., especially among patients without an acute ST-Elevation myocardial infarction (STEMI), may be encouraged by the generous reimbursement for interventional procedures as compared with medical therapy, which may unintentionally promote overuse of PCI. 7,8 In addition, policy makers and health economists have suggested that complex financial ties between physicians and hospitals may provide additional financial incentives to perform PCI in patients who could be treated effectively with medical therapy alone.…”
Section: Introductionmentioning
confidence: 99%
“…1 In the United States (U.S.) alone, an estimated 600,000 PCIs are performed annually at a direct cost of approximately $30 billion, 2-4 with similar trends in Europe and Canada. 5-7 The growth of PCI in the U.S., especially among patients without an acute ST-Elevation myocardial infarction (STEMI), may be encouraged by the generous reimbursement for interventional procedures as compared with medical therapy, which may unintentionally promote overuse of PCI. 7,8 In addition, policy makers and health economists have suggested that complex financial ties between physicians and hospitals may provide additional financial incentives to perform PCI in patients who could be treated effectively with medical therapy alone.…”
Section: Introductionmentioning
confidence: 99%